Pengaruh Food Quality dan Kesesuaian Harga Terhadap Kepuasan Konsumen (Studi Kasus: Gaembull Korean and Japanese Restaurant Barbeque All You Can Eat Cabang Bintaro) - Regina Dewi Hanifah (Akademi Pariwisata Bunda Mulia, 2019)
ABSTRACTThe increase in culinary business in the last few years has become a reinforcement for entrepreneurs in the food and beverage sector. It also forces culinary entrepreneurs to be more creative in offering their main products to compete with other culinary businesses. One of them is the increasing number of restaurants that offer a buffet style concept or commonly known by our society as